Studying enterococci isolated from artisanal feta produced with mountain and low land milk - Psomas, E; Sakaridis, I; Boukouvala, E; Papatsaroucha, E; Apostolidi, ED; Skarlatoudi, T; Ekateriniadou, LV; Samouris, Georgios (Journal of the Hellenic Veterinary Medical Society, 2024)
Enterococci are commonly part of natural milk cultures that are used to produce cheese and have a strong influence on ripening, and aroma development in feta cheese. Despite their unique benefits in cheese production, Enterococci have also been identified as opportunistic pathogens that can cause various human diseases and their use remains controversial due to the possibility of antimicrobial resistance transfer to human strains. The objective of the present study was to detect, identify, and analyze characteristics of Enterococcus spp. from different samples of the artisanal feta cheese produced with mountain or low land milk and finally to evaluate its potential use for enhancing the sensory characteristics of fermented milks and cheeses without compromising the safety of the products. Twenty-five strains of enterococci from mountain areas and twenty-five from low land areas were selected from the cheesemaking trials. Based on the desired technological characteristics, twelve strains were selected for analytical identification, study of antibiotic resistance and further study by molecular techniques. Eleven of those were found to be sensitive to vancomycin (lower to 10μg/ml), one was resistant up to 20μg/ml and therefore are even more promising, in terms of their safety, for their potential use as adjunct cultures and worth further analysis.